Women who opt out : the debate over working mothers and work-family balance - Jones, Bernie D. (NYU Press, 2012)
In a much-publicized and much-maligned 2003 New York Times article, "The Opt-Out Revolution," the journalist Lisa Belkin made the controversial argument that highly educated women who enter the workplace tend to leave upon marrying and having children. Women Who Opt Out is a collection of original essays by the leading scholars in the field of work and family research, which takes a multi-disciplinary approach in questioning the basic thesis of "the opt-out revolution." The contributors illustrate that the desire to balance both work and family demands continues to be a poi